The Complement System in the Pathophysiology of Pregnancy and in Systemic Autoimmune Rheumatic Diseases During Pregnancy - Chighizola, Cecilia Beatrice; Lonati, Paola Adele; Trespidi, Laura; Meroni, Pier Luigi; Tedesco, Francesco (Frontiers in Immunology, 2020)
The complement system plays a double role in pregnancy exerting both protective and damaging effects at placental level. Complement activation at fetal-maternal interface participates in protection against infectious agents and helps remove apoptotic and necrotic cells. Locally synthesized C1q contributes to the physiologic vascular remodeling of spiral arteries characterized by loss of smooth muscle cells and transformation into large dilated vessels. Complement activation triggered by the inflammatory process induced by embryo implantation can damage trophoblast and other decidual cells that may lead to pregnancy complications if the cells are not protected by the complement regulators CD55, CD46 and CD59 expressed on cell surface. However, uncontrolled complement activation induces placental alterations resulting in adverse pregnancy outcomes. This may occur in pathological conditions characterized by placental localization of complement fixing antibodies directed against beta2-glycoprotein 1, as in patients with anti-phospholipid syndrome, or circulating immune complexes deposited in placenta, as in patients with systemic lupus erythematosus. In other diseases, such as preeclampsia, the mechanism of complement activation responsible for complement deposits in placenta is unclear. Data on placental localization of complement components in placenta in other autoimmune diseases including rheumatoid arthritis, systemic sclerosis and Sjögren’s syndrome are not available. Conflicting results have been reported on the relevance of complement assays as diagnostic and prognostic tools to assess complement involvement in pregnant patients with these disorders.